Optical coherence tomography angiography findings in patients undergoing transcorneal electrical stimulation for treating retinitis pigmentosa - Zabek, Olga (Graefes Arch Clin Exp Ophthalmol, 2020)
PURPOSE: Transcorneal electrical stimulation (TES) is a novel treatment approach for patients with retinitis pigmentosa (RP). The aim of our study was to observe changes in optical coherence tomography angiography (OCTA) that would be attributed to TES treatment. METHODS: A total of 73 eyes were included: 43 eyes of 22 subjects (11 ♀, 11 ♂) suffering from RP were examined at baseline (BL), after first stimulation (TS), 1 week (1W), and 6 months (6M) after treatment initiation and were compared with 30 control eyes of 15 subjects (8 ♀, 7 ♂). TES was performed simultaneously on both eyes for 30 min weekly. OCTA scans of 9 × 15 mm were recorded with a PLEX Elite 9000 swept-source OCTA device (Carl Zeiss Meditec AG, Jena). Vascular density metrics such as perfusion density (PD) and vessel density (VD) were calculated automatically for the macular area by using standardised extended early treatment diabetic retinopathy study (ETDRS) grids centred around the fovea. In addition, the capillary perfusion density (CPD) and the capillary flux index (CFI) of the peripapillary nerve fibre layer microvasculature in all four quadrants of an annulus centred at the optic disc were measured. All parameters were determined over all retinal layers and separately for the superficial (SCP) and deep capillary plexus (DCP). ANOVA-based linear mixed-effects models were calculated with SPSS®. RESULTS: Throughout the course of TES treatment, the macular VD and PD of all retinal layers in all subsections showed a slight decrement without reaching statistical significance, also when analysed separately in the SCP and DCP (p > 0.08). In analogy, the average CPD and CFI also presented with a slight decrement (p > 0.20). However, when compared with controls, most OCTA parameters showed a significant decrement (p < 0.05). When analysed systematically in all subsections of the extended ETDRS grid, the temporal macular subsections within the outer ring (radius 1.5–3 mm) and also of the peripheral C1, C2, and C3 rings (radius 3–7.5 mm) showed lower VD and PD values when compared with the other subsections (p < 0.05). CONCLUSION: Vascular density metrics in the macular region and the peripapillary microvasculature appear to remain unaffected by continuous TES treatment within a period of 6 months. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00417-020-04963-7) contains supplementary material, which is available to authorized users.